Screening Chemicals for Receptor‐Mediated Toxicological and Pharmacological Endpoints: Using Public Data to Build Screening Tools within a KNIME Workflow. Issue 2 (20th February 2015) - Steinmetz, F. P.; Mellor, C. L.; Meinl, T.; Cronin, M. T. D.
Abstract: Assessing compounds for their pharmacological and toxicological properties is of great importance for industry and regulatory agencies. In this study an approach using open source software and open access databases to build screening tools for receptor‐mediated effects is presented. The retinoic acid receptor (RAR), as a pharmacologically and toxicologically relevant target, was chosen for this study. RAR agonists are used in the treatment of a number of dermal conditions and specific types of cancer, such as acute promyelocytic leukemia. However, when administered chronically, there is strong evidence that RAR agonists cause hepatosteatosis and liver injury. After compiling information on ligand‐protein‐interactions, common substructures and physico‐chemical properties of ligands were identified manually and coded into SMARTS strings. Based on these SMARTS strings and calculated physico‐chemical features, a rule‐based screening workflow was built within the KNIME platform. The workflow was evaluated on two datasets: one with RAR agonists exclusively and another large, chemically diverse dataset containing only a few RAR agonists. Possible modifications and applications of screening workflows, dependent on their purpose, are presented. Abstract :